Pengaruh Konseling Diet Jantung Terhadap Pengetahuan Diet Jantung Pasien Congestive Heart Failure (CHF) - Rispawati, Baik Heni (Universitas Fort De Kock Bukittinggi, 2019)
From World Health Organization (WHO) in 2016 asserted that in 2015 around 23 million or about 54% people deaths caused of Congestive Heart Failure (CHF). World civilization, technology, increasing of prosperity,economic growth influence the incidences and types of disease.That case can cause some diseases one of them are Congestive Heart Failure (CHF). Objective of the research is to determine the Effects of heart diet toward the knowledge of Congestive Heart Failure (CHF). Type of research is pre experiment with one group pretest posttest approach.Technique of data collection used inthis research using purposive sampling with 33 respondents. In taking data of the research using questionnaire which consists of 12 questions for each respondent. Results obtained from 33 respondents,the average value of knowledge before being given cardio diet counseling around 47.87 and it changed to 63.63 and then after being given cardio diet counseling the count value shows the number 13.656 or higher than t table around 1.697 2.Average level of patients knowledge with heart failure categorized enough categories. People are expected to know the benefits of heart failure diet so it can control the eating pattern while balanced with doing activities and healthy lifestyle,it can recovery the heart condition more healthy.Keywords: Knowledge of Heart Diet, Congestive Heart Failure (CHF), Heart Diet Counseling